2010
DOI: 10.1111/j.1745-9125.2010.00203.x
|View full text |Cite
|
Sign up to set email alerts
|

Racial–ethnic Intolerance and Support for Capital Punishment: A Cross‐national Comparison*

Abstract: This article tests cross‐nationally the minority group threat thesis that public sentiments toward repressive crime‐control policies reflect conflicted racial and ethnic relations. Using multiple data sets representing France, Belgium, the Netherlands, East and West Germany, Italy, Luxembourg, Denmark, Great Britain, Greece, Spain, Finland, Sweden, Austria, Canada, Ireland, and Portugal, we examine whether racial and ethnic intolerance—animus, resentments, or negative sentiments toward minorities—predicts grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
115
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(121 citation statements)
references
References 96 publications
6
115
0
Order By: Relevance
“…Kornhauser (2013) examined data obtained from a sample of 998 respondents who completed the Australian Survey of Social Attitudes (AuSSA) (2005) (Wilson, Gibson, Meagher, Denemark, & Western, 2006). Kornhauser's results support international findings that racial animus towards immigrants, significantly predicts support for punitive attitudes (Unnever & Cullen, 2010a). …”
supporting
confidence: 81%
See 1 more Smart Citation
“…Kornhauser (2013) examined data obtained from a sample of 998 respondents who completed the Australian Survey of Social Attitudes (AuSSA) (2005) (Wilson, Gibson, Meagher, Denemark, & Western, 2006). Kornhauser's results support international findings that racial animus towards immigrants, significantly predicts support for punitive attitudes (Unnever & Cullen, 2010a). …”
supporting
confidence: 81%
“…In the USA, a content analysis of the news presented on three television stations in Florida, revealed that Hispanics were more likely to appear as criminal suspects (Chiricos & Eschhalz, 2002). Media coverage is a contributing factor to cotemporary negative perceptions of the Muslim community (Abdalla & Rane, 2008), and there is growing public association of "immigrant others" with crime (Unnever & Cullen, 2010a). Findings from the present study, although exploratory, lend support for the theory that crime has largely been typified as an "out group" phenomenon (Chiricos et al, 2004).…”
Section: Subtle Differences In Contemporary Media Coverage Of New-immmentioning
confidence: 41%
“…Unnever and Cullen, 2010a) that the racial animus explanation applies cross-nationally, here in relation to animus towards migrants in Australia. Respondents who scored highly on the Anti-immigrant Sentiment index were more likely to support both measures of punitiveness.…”
Section: Discussionmentioning
confidence: 93%
“…This body of empirical inquiry provides valuable insights into the social and psychological correlates of support for capital punishment not just in America but other countries as well (see, e.g., Unnever and Cullen ). However, it does not address variation at the case level.…”
Section: Literature Reviewmentioning
confidence: 99%